2017
DOI: 10.6033/tokkyou.55.201
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Tracking Measure of Responsiveness to Joint Attention: Validity and Clinical Usefulness With Young Children With Autism Spectrum Disorder

Abstract: Falck-Ytter et al. 2012 ASD RJA Falck-Ytter et al. 2012 RJA RJA Navab et al. 2012 Joint attention is one predictor of later social-communication behaviors of children with autism spectrum disorder. In the present study, joint attention behavior was divided into 2 categories: initiating joint attention (IJA), including the child's pointing, and responsiveness to joint attention (RJA), including gaze-following and pointing-following. Recently, research on eye-tracking responsiveness to joint attention in babies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…We based our use of stimuli movies (Fig. 1) and RJA evaluation on a previous study, which found that eye-tracking provides a useful measure of RJA (Nagai, Hinobayashi, & Kanazawa, 2017b). Each stimulus began with a scene of a female model sitting behind a table and facing the camera.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…We based our use of stimuli movies (Fig. 1) and RJA evaluation on a previous study, which found that eye-tracking provides a useful measure of RJA (Nagai, Hinobayashi, & Kanazawa, 2017b). Each stimulus began with a scene of a female model sitting behind a table and facing the camera.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…e principal measurement of gaze-following determined whether the rst eye-movement saccade from the head toward an object during the gaze-following condition step or the point-following condition step moved toward the object at which the model looked at (correct responsiveness) or toward the other object (incorrect responsiveness). We then analyzed the gaze behaviors by using both an "area of interest (AOI)" setting and a "gaze plot" function to judge whether the participants' gaze xation moved from the model (RJA cue) to the toy (object of the Figure 2 shows the AOI setting and visual angle for each condition, following Nagai, Hinobayashi, and Kanazawa, (2017b). We also used AOI analysis tools to calculate where and for how long the participants xed their eye gaze in each step.…”
Section: Outcome Measuresmentioning
confidence: 99%